Development of isocratic RP-HPLC method for separation and quantification of L-citrulline and L-arginine in watermelons - Ridwan, Rasdin; Abdul Razak, Hairil Rashmizal; Adenan, Mohd Ilham; Md Saad, Wan Mazlina (Hindawi, 2018)
Watermelons (Citrullus lanatus) are known to have sufficient amino acid content. In this study, watermelons grown and consumed in Malaysia were investigated for their amino acid content, L-citrulline and L-arginine, by the isocratic RP-HPLC method. Flesh and rind watermelons were juiced, and freeze-dried samples were used for separation and quantification of L-citrulline and L-arginine. Three different mobile phases, 0.7% H3P04, 0.1% H3P04, and 0.7% H3P04 : ACN (90 : 10), were tested on two different columns using Zorbax Eclipse XDB-C18 and Gemini C18 with a flow rate of 0.5 mL/min and a detection wavelength at 195 nm. Efficient separation with reproducible resolution of L-citrulline and L-arginine was achieved using 0.1% H3P04 on the Gemini C18 column. The method was validated and good linearity of L-citrulline and L-arginine was obtained with = 0.9956, and , , respectively. L-citrulline content showed the highest concentration in red watermelon of flesh and rind juice extract (43.81 mg/g and 45.02 mg/g), whereas L-arginine concentration was lower than L-citrulline, ranging from 3.39 to 11.14 mg/g. The isocratic RP-HPLC method with 0.1% H3P04 on the Gemini C18 column proved to be efficient for separation and quantification of L-citrulline and L-arginine in watermelons.